Lungenembolie - Hecker, Matthias; Weigand, Markus A. (Der Anaesthesist, 2017)
Pulmonary embolism is a potentially fatal disorder and frequently seen in critical care and emergency medicine. Due to a high mortality rate within the ﬁrst few hours, the accurate initiation of rational diagnostic pathways in patients with suspected pulmonary embolism and timely consecutive treatment is essential. In this review, the current European guidelines on the diagnosis and therapy of acute pulmonary embolism are presented. Special focus is put on a structured patient management based on the individual risk of early mortality. In particular risk assessment and new risk-adjusted treatment recommendations are presented and discussed in this article.